Prediksi Umur Simpan Selada Romaine Potong (Lactuca Sativa Var. Longifolia) Berdasarkan CIE a* Menggunakan Metode Arrhenius - Drupadi Ciptaningtyas; Shitah Khoerunnisa; Lukito Hasta Pratopo; Ahmad Thoriq (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Fresh-cut romaine lettuce undergoes physical changes that make it more susceptible to spoilage and reduce its shelf life. To maintain its quality and extend shelf life, several technologies can be applied, including fine bubble washing, blue LED irradiation, and low-temperature storage. Estimating the shelf life under these treatments is essential, as shelf life is a critical factor in food product quality and safety. This study aimed to predict the shelf life of fresh-cut romaine lettuce treated with fine-bubble washing and blue LED irradiation using the Arrhenius model. Shelf life estimation was conducted under various storage conditions: room temperature, 8°C, and 5°C for up to 6 days. The Arrhenius model was used based on the CIE a* color parameter as an indicator of quality degradation. The results showed that the optimal treatment for extending shelf life was storage at 5°C without fine-bubble washing or LED irradiation, which resulted in an estimated shelf life of up to 42 days.